Giving virtual world learning a pedagogical boost with a gamified authentic learning design - Teräs, H.; Teräs, Marko; Reiners, Torsten (AACE, 2014)
Gamification is one of today’s hot topics in education. However, the concept is new and sometimes gets mixed up with others, such as virtual worlds or game-based learning. Understanding of what gamification actually is and what the educational benefits are is also diverse. The nDiVE research team explores how learning work related skills in supply chain management with the help of immersive virtual worlds can be supported with a learning design building on elements of gamification and the pedagogical framework of authentic learning. The complexity of supply chains and the related skills cannot be fully acquired from textbooks or other traditional ways of teaching and learning. There is also an identified gap in graduate skills and organisational expectations. While immersive virtual worlds can be extremely useful in that they can take students to learning situations that otherwise would not be safe, feasible or cost-effective, it is important not to let cutting edge technology steal the show. Instead, a pedagogically sound learning design should be employed to ensure a beneficial learning experience. Authentic learning provides a useful design framework for gamified learning experiences in a virtual world.